2020
DOI: 10.3390/microorganisms9010072
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein–Barr Virus in Periodontitis: A Review of Methodological Approaches

Abstract: Periodontitis, an inflammatory condition that affects the structures surrounding the tooth eventually leading to tooth loss, is one of the two biggest threats to oral health. Beyond oral health, it is associated with systemic diseases and even with cancer risk. Obviously, periodontitis represents a major global health problem with significant social and economic impact. Recently, a new paradigm was proposed in the etiopathogenesis of periodontitis involving a herpesviral–bacterial combination to promote long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 100 publications
0
9
0
1
Order By: Relevance
“…A recent study found that latent membrane protein 1, encoded by EBV, induces IL8 production, which promotes the progression of periodontitis in human gingival cells (Watanabe et al, 2019). However, the role of EBV in the etiology of periodontitis has not been clarified (Imai and Ogata, 2020;Tonoyan et al, 2020). In summary, the roles of viruses in oral diseases are extremely important.…”
Section: Relationships Between Oral Microorganisms and Oral Diseasesmentioning
confidence: 99%
“…A recent study found that latent membrane protein 1, encoded by EBV, induces IL8 production, which promotes the progression of periodontitis in human gingival cells (Watanabe et al, 2019). However, the role of EBV in the etiology of periodontitis has not been clarified (Imai and Ogata, 2020;Tonoyan et al, 2020). In summary, the roles of viruses in oral diseases are extremely important.…”
Section: Relationships Between Oral Microorganisms and Oral Diseasesmentioning
confidence: 99%
“…The transcriptional promoter of LMP (LMPp) is located in the BamH I N region, which is transactivated by EBNA2, and EBNA2 induces the expression of LMPs (Kartika et al 2020). The EBV lytic cycle is initiated by the activation of two promoters, the BZLF1 promoter (Zp) and BRLF1 promoter (Rp), that direct the expression of the immediate-early genes Zta and Rta, which in turn activate the downstream lytic genes individually or coordinately (Jin et al 2010;Tonoyan et al 2020).…”
Section: Dna Methylation Of the Ebv Genomementioning
confidence: 99%
“…In tumor biopsy samples, the gold standard technique for detecting latent EBV is in situ hybridization (ISH) using DNA or RNA probes specific to EBV-encoded RNA (EBERs) ( Fanaian et al., 2009 ; AbuSalah et al., 2020 ). Given the abundant expression (in millions of copies) of EBERs in latently-infected cells, they serve as dependable molecular markers crucial for detecting and localizing EBV-infected tissue samples ( AbuSalah et al., 2020 ; Tonoyan et al., 2020 ). Nevertheless, the drawbacks of complex, tedious, and time-consuming procedures with a high possibility of obtaining false negative results restrict its extensive utilization in clinical diagnosis ( AbuSalah et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method facilitates the real-time monitoring and quantification of amplified targeted nucleic acid sequences by employing either fluorescent probes or an intercalating dye, based on amplifying a conserved sequence. ( AbuSalah et al., 2020 ; Tonoyan et al., 2020 ). Although highly sensitive, specific, and efficient, PCR-based techniques require complex thermal cycling apparatus for target DNA amplification and need gel electrophoresis or probe hybridization techniques for result analysis, hindering its widespread use in resource-limited regions ( Wang et al., 2016a ; Wang et al., 2016b ; Yuan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%